The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2165/11531770-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of a Fixed-Dose Combination of Metoprolol Extended Release/Amlodipine in Patients with Mild-to-Moderate Hypertension

Abstract: Metoprolol XL/amlodipine fixed-dose combination was found to be as effective and well tolerated as losartan plus amlodipine in the treatment of essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In patients who had undergone bariatric surgery, about 8% showed complete remission of diabetes while more than 90% showed a significant decrease in their insulin or OADs requirement [62]. & Laparoscopic sleeve surgery and RYBG were found to be safe and effective treatment options among obese Indian population with T2DM with significant remission rates (> 95%, p < 0.001), larger reductions in A1C, and diabetes medication usage [63][64][65]. [1,2] in consonance with ADA [3].…”
Section: Pharmacotherapy For Obese T2dmmentioning
confidence: 93%
See 2 more Smart Citations
“…In patients who had undergone bariatric surgery, about 8% showed complete remission of diabetes while more than 90% showed a significant decrease in their insulin or OADs requirement [62]. & Laparoscopic sleeve surgery and RYBG were found to be safe and effective treatment options among obese Indian population with T2DM with significant remission rates (> 95%, p < 0.001), larger reductions in A1C, and diabetes medication usage [63][64][65]. [1,2] in consonance with ADA [3].…”
Section: Pharmacotherapy For Obese T2dmmentioning
confidence: 93%
“…& Interventions predominantly based on counselling and education are found to be effective in preventing/reducing the risk of developing diabetes and its complication and also helps in improving dietary patterns of individuals with prediabetes and diabetes [31,62]. Mobile phone messaging was found to be an inexpensive and most effective alternative way to deliver educational and motivational advice and support towards lifestyle modification in high-risk individuals [63]. & Dietary interventions such as high-carbohydrate low-fat diet [64], fiber-rich [65], and protein-rich diet [66,67]…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…[ 285 ] Furthermore, some patients require a combination of two drugs in order to achieve a recommended BP target. Several Indian studies evaluated the efficacy of some FDCs: losartan 50 mg plus ramipril 2.5 mg vs each alone,[ 587 ] metoprolol extended release (XL) plus amlodipine vs losartan plus amlodipine,[ 588 ] metoprolol and amlodipine,[ 589 ] and reported that the FDCs were effective, safe and well-tolerated in patients with hypertension. …”
Section: Anagementmentioning
confidence: 99%
“… 91 A fixed dose combination of metoprolol extended release with amlodipine was as effective, and well tolerated as a combination of losartan and amlodipine in reducing both SBP and DBP. 92 However, combining carvedilol extended release with lisinopril was not superior to monotherapy with the either drug, except in high dose combinations, despite producing additional reduction in 24-hour mean DBP. 93 Adding nebivolol to resistant stage I-II hypertensive patients undergoing antihypertensive therapy significantly improves the response and control rate.…”
Section: Beta-blocker Combinationsmentioning
confidence: 93%